Gleeful UMP Language and Cultural Carnival - Mimi Rabita, Abdul Wahit (2023)
PAYA BESAR, 17 December 2022 - The organisation of the Language and Cultural Carnival by the Centre for Modern Languages (CML) in collaboration with the Centre for International Relations (CIR), Universiti Malaysia Pahang (UMP) could fuel students’ love for language and culture while strengthening their confidence in communicating and understanding the culture of different countries.